2002
DOI: 10.1038/sj.onc.1205974
|View full text |Cite
|
Sign up to set email alerts
|

Groups of p53 target genes involved in specific p53 downstream effects cluster into different classes of DNA binding sites

Abstract: The tumor suppressor protein p53, once activated, can cause either cell cycle arrest or apoptosis through transactivation of target genes with p53 DNA binding sites (DBS). To investigate the role of p53 DBS in the regulation of this profound, yet poorly understood decision of life versus death, we systematically studied all known and potential p53 DBS. We analysed the DBS separated from surrounding promoter regions in yeast and mammalian assays with and without DNA damage. p53 efficiently utilized the DBS of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 44 publications
11
118
0
Order By: Relevance
“…Only experiments with high levels of p53 showed a significant increase of DNA binding (Figure 1). These data are supported by recent in vivo analyses indicating that p53 binding and transactivation via the bax response element is very weak compared to WAF or mdm2 (Inga et al, 2002;Qian et al, 2002). Furthermore, both studies showed that the transcriptional activation of WAF1 promoter by p53 is two to five times stronger than for mdm2 promoter, supporting the results of our in vitro studies.…”
Section: Published Online 7 June 2004supporting
confidence: 81%
“…Only experiments with high levels of p53 showed a significant increase of DNA binding (Figure 1). These data are supported by recent in vivo analyses indicating that p53 binding and transactivation via the bax response element is very weak compared to WAF or mdm2 (Inga et al, 2002;Qian et al, 2002). Furthermore, both studies showed that the transcriptional activation of WAF1 promoter by p53 is two to five times stronger than for mdm2 promoter, supporting the results of our in vitro studies.…”
Section: Published Online 7 June 2004supporting
confidence: 81%
“…At present, little is known about how the epigenetic network interacts with other transcriptional machineries to regulate gene expression in mammalian cells. In the past, p53-binding motifs with GC rich features were observed in several gene promoters including EGFR, Killer/DR4, RB and TGF-a (Qian et al, 2002). However, there are fundamental questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…This "half-site" sequence is separated from another half-site by 0 to 13 bp in most cases. However, a number of known p53 targets are regulated through a broad range of degenerate sequences (66), making the identification of functional p53REs potentially problematic. In order to individually confirm p53 association with selected promoters, we first identified potential p53REs in the vicinity of identified CGIs.…”
Section: Resultsmentioning
confidence: 99%